2019
DOI: 10.33723/rs.543715
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Umutsuzluk Düzeyi̇ Ve Bi̇li̇şsel Çarpitmalari Üzeri̇ne Bi̇r Araştirma

Abstract: Araştırmanın amacı, üniversite öğrencilerinin bilişsel çarpıtma ve umutsuzluk düzeylerini (ve üç alt boyutunu) sosyo-demografik değişkenler açısından incelemektir. Bilişsel çarpıtmalar kişilerin geleceğe yönelik beklentileri, sorun çözme yöntemlerini ve çevreye uyum sürecini olumsuz yönde etkileyerek bireylerde umutsuzluğa neden olmaktadır. Bu amaçla araştırmaya lisans öğrencisi olan 54 öğrenci dâhil edilmiştir. Katılımcılara yirmi sorudan oluşan Beck Umutsuzluk Ölçeği (BUÖ), on beş sorudan oluşan Bilişsel Çar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition to that, some negative state of emotions can have an influence over entrepreneurial intention. The negative state of emotions which are observed in the vast majority of a society (Duman, İmre & Mısırlı, 2019) and the consequences of which are still not known precisely cannot take individuals' imagination away from them completely, and can enable them to perform very powerful behaviors in appropriate conditions (Hyroop, 1953). Such apprehensions as finding a job in the future can ensure the emergence of intentions related to entrepreneurship which will reverse the existing situation and provide the acquisition of a significant status in a society.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, some negative state of emotions can have an influence over entrepreneurial intention. The negative state of emotions which are observed in the vast majority of a society (Duman, İmre & Mısırlı, 2019) and the consequences of which are still not known precisely cannot take individuals' imagination away from them completely, and can enable them to perform very powerful behaviors in appropriate conditions (Hyroop, 1953). Such apprehensions as finding a job in the future can ensure the emergence of intentions related to entrepreneurship which will reverse the existing situation and provide the acquisition of a significant status in a society.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted with students from the faculty of education, the SFT skills of female students were at a higher level (14). Bilgiç et al (15) found that nursing stu-dents and Duman et al (16) found that university students have high levels of hope.…”
Section: Introductionmentioning
confidence: 99%